Development Of Interactive Learning Simulator For Process Control Using Matlab/Simulink - Md Yusof, Mohamad Muhaimin (Universiti Sains Malaysia, 2018)
Teaching process control course to undergraduate chemical engineering can be very challenging due to difficulty to understand the theory of process control and to relate the course with the industry application. This study focuses on how adaptation of training simulator for education purposes, use of pre-simulation and post-simulation survey to measure the effectiveness of the training simulator. The training simulator was done to motivate the students to learn the process control and also to enhance interactive learning in process control. Pre-simulation survey was used to obtain students’ opinions regarding process control subject. From the analysis of survey, it give an idea on how to make the teaching of process control become interesting by creating a simulation program using MATLAB Simulink that works based on real-time. Also in this work, the developments of simulation of vacuum evaporator using MATLAB Simulink were validated by compare the result from simulation with literature. Lastly, post-simulation surveys were done when the training simulator has been finished to test the efficiency of training simulator. The result from the survey and quiz shows that majority of the students are able to enhance their understanding on process control subject by using the training simulator and majority of them able to answer the quiz correctly with mean 4.1 (Standard Deviation, SD = 12.88) and 3.4 (SD = 8.98) respectively for the participants that have learnt process control and participants that do not learnt process control.